2013
DOI: 10.5424/sjar/2013111-2686
|View full text |Cite
|
Sign up to set email alerts
|

Alternative rooting induction of semi-hardwood olive cuttings by several auxin-producing bacteria for organic agriculture systems

Abstract: Southern Spain is the largest olive oil producer region in the world. In recent years organic agriculture systems have grown exponentially so that new alternative systems to produce organic olive cuttings are needed. Several bacterial isolates, namely Pantoea sp. AG9, Chryseobacterium sp. AG13, Chryseobacterium sp. CT348, Pseudomonas sp. CT364 and Azospirillum brasilense Cd (ATCC 29729), have been used to induce rooting in olive semi-hardwood cuttings of Arbequina, Hojiblanca and Picual cultivars of olive (Ole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
1
21
0
4
Order By: Relevance
“…Bacteria containing ACC-deaminase with a potential effect on growth of maize under saline conditions were also isolated and characterized by Hussain et al ( 2013 ). Montero-Calasanz et al ( 2013 ) confi rmed, that the inoculation of Pantoea sp. AG9, Chryseobacterium sp.…”
Section: Acc-deaminase and Halotolerant Pgpbmentioning
confidence: 93%
“…Bacteria containing ACC-deaminase with a potential effect on growth of maize under saline conditions were also isolated and characterized by Hussain et al ( 2013 ). Montero-Calasanz et al ( 2013 ) confi rmed, that the inoculation of Pantoea sp. AG9, Chryseobacterium sp.…”
Section: Acc-deaminase and Halotolerant Pgpbmentioning
confidence: 93%
“…In recent years the European Commission imposed restrictions on the use of chemicals, including auxins, in plant production. Therefore, searching for root-promoting substances and exploitation of natural biostimulators is one of strategies aimed at improving the rooting efficiency with a simultaneous reduction of the use of exogenous auxins (Arthur et al 2004;Pacholczak et al 2012a, b;Montero-Calasanz et al 2013). The application of natural products during commercial rooting may also limit the losses caused by poor quality of the root system or of the shoot, caused by auxin used in the rooting treatment (De Klerk et al 1999;Kakani et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Drought tolerance of Macadamias improves when mycorrhized (Yooyongwech et al 2013). Similarly, we could not find any information concerning the effect of PGPR on the quality of O. europaea fruits; actually, the only report concerns the rooting induction of some auxin-producing bacteria on olive cuttings (Montero-Calasanz et al 2013). Olive trees can form arbuscular mycorrhiza (Citernesi et al 1998) although species-specific responses have been reported: three different cultivars of olive plants have been found to be colonized by a Gigaspora species, but only one of the three by a Glomus species (Chatzistathis et al 2013).…”
Section: 3mentioning
confidence: 63%